Femoral cementation in knee arthroplasty: a comparison of three cementing techniques in a sawbone model using the ATTUNE knee - Schwarze, Martin; Schonhoff, Mareike; Beckmann, Nicholas A.; Eckert, Johannes A.; Bitsch, Rudi G.; Jäger, Sebastian (The journal of knee surgery, 2021)
Femoral component loosening is a rare but severe complication in total knee arthroplasty. Former studies have repeatedly demonstrated radiolucent lines behind the ventral and dorsal anchoring shields of the femoral components, which has led us to investigate this matter further. Therefore, three different cementing techniques were tested in a group of nine Sawbone samples each. These differed in the amount of cement applied on the femoral component as well as in the pressure application. Computed tomography was performed to evaluate and classify the cement penetration into the bone adjacent to the prosthesis according to the zones defined by the Knee Society scoring system. The results show significantly deeper cement penetration in all zones when a pressurizer is used. In the other two groups, no significant difference in the dorsal bevel cement penetration was noted. Additionally, no difference in ventral and dorsal cement penetrations (Zones 1 and 4) was delineated. In contrast, there was a significant difference in both the ventral bevel (Zone 2) as well as the distal anchoring surface (Zones 5-7). The use of a pressurizer results in greater cement penetration into all anchoring areas. Completely covering the component back surface results in a significantly higher penetration, which is mainly due to differences in volume. These data show significantly improved cementation results when using a pressurizer. Whether this improves the biomechanical properties and ultimately the revision rate requires further investigation.
Publikationsdatum: 21. August 2019 (online)
Gesehen am 07.04.2021